Platelet-Derived Microvesicles Promote VSMC Dedifferentiation After Intimal Injury via Src/Lamtor1/mTORC1 Signaling - Liu, Ji-Ting; Bao, Han; Fan, Yang-Jing; Li, Zi-Tong; Yao, Qing-Ping; Han, Yue; Zhang, Ming-Liang; Jiang, Zong-Lai; Qi, Ying-Xin (Frontiers in Cell and Developmental Biology, 2021)
Phenotypic switch of vascular smooth muscle cells (VSMCs) is important in vascular remodeling which causes hyperplasia and restenosis after intimal injury. Platelets are activated at injured intima and secrete platelet-derived microvesicles (PMVs). Herein, we demonstrated the role of PMVs in VSMC phenotypic switch and the potential underlying mechanisms. In vivo, platelets were locally adhered and activated at intimal injury site, while Lamtor1 was promoted and VSMCs were dedifferentiated. PMVs, collected from collagen-activated platelets in vitro which mimicked collagen exposure during intimal injury, promoted VSMC dedifferentiation, induced Lamtor1 expression, and activated mTORC1 signaling, reflected by the phosphorylation of two downstream targets, i.e. S6K and 4E-BP1. Knockdown of Lamtor1 with small interfering RNA attenuated these processes induced by PMVs. Based on the previously published proteomic data, Ingenuity Pathway Analysis revealed that Src may participate in regulating effects of PMVs. Src inhibitor significantly reversed the effects of PMVs on VSMC dedifferentiation, Lamtor1 expression and mTORC1 activation. Furthermore, in SMC-specific Lamtor1 knockout mice, intimal hyperplasia was markedly attenuated after intimal injury compared with the wild type. Our data suggested that PMVs secreted by activated platelets promoted VSMC dedifferentiation via Src/Lamtor1/mTORC1 signaling pathway. Lamtor1 may be a potential therapeutic target for intimal hyperplasia after injury.